Factores limitantes para la aplicación de la facturación electrónica en los microempresarios de Contamana, 2023 - Pérez Rodríguez, José Luis (2024)
This final report aims to identify the limiting factors for the application of einvoicing in the micro-entrepreneurs of Contamana, 2023. An applied type study was applied, explanatory level with a non-experimental design, opting for a population of 258 microentrepreneurs to whom a survey with a questionnaire of questions was used, this for the collection of information. The results showed that the technological factor is the dependent variable that significantly generates a similar behavior in the face of its intervention; Likewise, e-invoicing is significant at the 0.000 level with 39.6%; business turnover explains its behavior by 23.1% with a sig. of 0.000; The personal factor shows a behavior of 12.7, contracted by a GIS of 0.000; Institutional turnover shows a behavior of 11.2% corroborated by a GIS of 0.000; Finally, e-invoicing shows a behavior of 6% and a sig. of 0.000.